KECENDERUNGAN PENELITIAN PENGUNGKAPAN ISR PADA GOOGLE SCHOLAR TAHUN 2022 - Rahmat Irfan; Muhammad Salman; Ainul Yusna Harahap; Rahmad Tantawi (Jurnal Mahasiswa Akuntansi Samudra, 2023)
Islamic Social Reporting (ISR) is the development of disclosure of social responsibility in accordance with sharia principles. This study uses content analysis of several articles that have been published in Googel Scholars throughout Indonesia in 2022, with the disclosure of Islamic Social Reporting (ISR) as the main focus. This study reveals the type of research with a quantitative approach with secondary data that is predominantly used by researchers who publish their journals on Google Scholar in 2022. Multiple linear regression tests and descriptive statistics are the instruments and data analysis methods most commonly used.